Three stations [large type] : an Arkady Renko novel - Smith, Martin Cruz, 1942- (Center Point Pub., 2010)
Struggling with a prosecutor's refusal to give him work, investigator Arkady Renko of Moscow finds his efforts to watch out for a teen chess prodigy challenged by a case involving a kidnapped baby, a dead prostitute, and police corruption.